It takes a community to train a future physician: social support experienced by medical students during a community-engaged longitudinal integrated clerkship (Canadian Medical Education Journal, 2019)
Background:Social support may be beneficial for medical students who must develop adaptive strategies to respond to the demands and challenges during third-year clerkship.We provide a detailed description of the supportive behaviours experienced by third-year students during a longitudinal integrated clerkship (LIC) in the context of rural family medicine.Methods:Informed by a social constructivist research paradigm, we undertook a qualitative study to understand from the students’ perspectives the presence and characteristics of social support available during a LIC.Data were collected from conversational interviews at three points during the eight-month clerkship year, pre-, during, and post-clerkship, to explore how 12 medical students experienced social support. We employed an innovative methodological approach, the guided walk method, to gain the students’ stories in the contexts where they were taking place.Results: The participants described the relationships they developed with various sources of social support such as (a) preceptors, (b) peers, (c) family, (d) health professionals, and (e) community members. Conclusion:Various individuals representing communities of practice such as the medical profession and community members were intimately related to the longitudinal aspects of the students’ experiences. The findings lend credence to the view that it really does take a community to train a future physician.